The role of small, micro and medium enterprises in job creation in South Africa - Jakuja, Nomahlubi (My University, 2017)
The role of SMMEs in job creation in developed countries has been studied extensively. These studies do not include micro firms in their research. There is a scarcity of literature when it comes to the role SMMEs play in job creation in developing countries. This study adds to the literature gap by incorporating micro firms in its research. The study explored the ability of SMMEs in addressing unemployment in South Africa by looking at their ability to create jobs. The study is a qualitative analysis of existing literature combined with interviews of 16 SMME owners. The role SMMEs play in job creation is not only measured by the number of people employed (labour intensiveness) but also by the potential of SMMEs to grow and thus create jobs in the future. The interview respondents were largely comprised of microenterprises. The paper also found business owners to have low and negative sentiments towards the government. Cash flow and funding remained the major challenges facing the sector in 2016/17. The findings from the interviews are aligned with the empirical findings of the study.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Management in the field of Public Policy, Johannesburg, 2017.
Keywords: Small business--South Africa; Job creation--South Africa